PENERAPAN PRINSIP KEHATI-HATIAN OLEH NOTARIS DALAM PERJANJIAN NOMINEE: (STUDI KASUS PUTUSAN NOMOR 4223 K/Pdt/2022) - Tri Agung Ariswanda (CV. KAMPUS AKADEMIK PUBLISING, 2024)
A nominee agreement made by a notary in the form of an authentic deed makes the agreement as perfect evidence and provides an important role in realizing legal certainty in freedom of contract as stated in Article 1338 of the Civil Code. The notary's negligence by not applying the prudence principle in making a nominee agreement will result in losses for both the parties and the notaries themselves. There are two problem formulations, namely one, how is the prudence principle applied by the Notary in the nominee agreement based on the Cassation Decision Case Number 4223 K/Pdt/2022? Two, what is the Notary's responsibility for nominee agreements based on Cassation Decision Case Number 4223 K/Pdt/2022? This research is a normative legal research which originates from secondary source and then processed descriptively qualitatively. In decision number 4223 K/Pdt/2022, the notary who made the nominee agreement appears not to have applied the principle of prudence maximumly create an agreement whose object violates the law. The Notary's carelessness will give rise to the Notary's liability which can then be requested in the form of administrative sanctions, civil sanctions and criminal sanctions.